Adherence to Antihypertensive Medication in Post-Stroke Patients: Patterns, Barriers, and Clinical Outcomes in a Prospective Cohort Study - Nitey, Prateek; Bhagat, Piyush; Sahare, Rinkita; Modak, Anil; Khurana, Kartik; Wani, Diksha (Journal of Neonatal Surgery, 2025)
Background: Medication adherence is crucial for secondary stroke prevention, yet non-adherence remains a significant challenge. This study evaluates adherence patterns, identifies key barriers, and assesses clinical outcomes in post-stroke patients receiving antihypertensive therapy. Methods: A prospective cohort study was conducted in a single tertiary care center, enrolling 150 post-stroke patients. Adherence was assessed using the 8-item Morisky Medication Adherence Scale (MMAS-8). Barriers to adherence were identified through structured questionnaires. Clinical outcomes, including blood pressure control, recurrent stroke, and cardiovascular events, were recorded over a 12-month follow-up. Statistical analyses included Chi-square tests, logistic regression, and Kaplan-Meier survival analysis. Results: Only 36% of patients exhibited high adherence, while 32% had moderate and 32% had low adherence. Key barriers included forgetfulness (42%), fear of side effects (28%), and cost-related constraints (25%). Patients with low adherence had a 3.2-fold increased risk of recurrent stroke (p = 0.002). Blood pressure control was achieved in 85% of high-adherence patients versus 29% in the low-adherence group (p < 0.001). Conclusion: Adherence to antihypertensive therapy remains suboptimal in post-stroke patients, contributing to poor clinical outcomes. Targeted interventions addressing barriers to adherence are essential to enhance secondary stroke prevention and improve patient survival